Prioritizing research on over-the-counter (OTC) hearing aids for age-related hearing loss - Manchaiah, Vinaya; Swanepoel, De Wet; Sharma, Anu (Frontiers in Aging, 2023)
Hearing aids are the most commonly used treatment for people with age-related hearing loss, however, hearing aid uptake is low, primarily due to high cost of the device, stigma, and a lack of perceived need. To address accessibility and affordability issues, the U.S. Food and Drug Administration created a new over-the-counter (OTC) hearing aid category. Various types of hearing devices are available for both individuals with hearing loss and for those with normal hearing, as hearing enhancement devices. Hearing aids (i.e., prescription hearing aids, self-fitting OTC hearing aids, and pre-set OTC hearing aids) are regulated by the FDA. The purpose of this article is to (a) provide a summary of existing research on direct-to-consumer (DTC) hearing devices such as Personal Sound Amplification Products (PSAPs) that informs OTC service delivery models; (b) provide an update on existing and ongoing randomized controlled trials on currently marketed OTC hearing aids; and (c) highlight the need for immediate research on OTC hearing aids and service delivery models to inform policy and clinical care. It remains to be seen what effect OTC hearing aids have on improving the uptake of hearing aids by individuals with mild-to-moderate hearing loss. However, there is scant research on all aspects of OTC hearing aids that are currently on the market. We conclude that high quality independent research must be prioritized to supplement evidence provided by the OTC hearing aid manufacturers for regulatory approval purposes.